Credibility and interactivity: Persuasive components of ideological group websites - Johnson, Genevieve; Taylor, W.; Ness, A.; Ault, M.; Dunbar, N.; Jensen, M.; Connelly, S. (2014)
The quickly growing presence of ideological groups on the Internet has garnered interest into how these groups use technology to persuade others. This study extends current research on the influential effects of website credibility and interactivity to the context of ideological group websites. Results of this study indicated that credibility and interactivity had direct and interactive effects on outcomes of agreement with the ideology, negative affective responses, and strength of argument when responding to the website. A number of these results may be due to (in)consistency with previous beliefs or violations of expectations regarding ideological group websites. Limitations and future directions are also discussed.